A patient-specific image-based approach to estimate pulmonary artery stiffness based on vessel constitutive model. (September 2022) - Begnis, Mattia; Chaar, Yasmine; Savoldelli, Anna; Scaburri, Andrea; D'Armini, Andrea M.; Valentini, Adele; Lanzarone, Ettore
Highlights: Patient-specific approach to estimate pulmonary artery stiffness based on MRI images. Maximum likelihood estimation approach that exploits a full vessel constitutive law. Young's modulus derived in terms of mean value and standard deviation. Entire boundary and an arc free from surrounding structures separately considered. Approach applied to pulmonary endarterectomy for treating thromboembolic hypertension. Abstract: An accurate non-invasive evaluation of the mechanical properties of the vessel wall is important for a variety of screening protocols and surgical treatments. In this work, we focused on a section of the Pulmonary Artery (PA), and developed a patient-specific approach to estimate its stiffness in terms of the Young's modulus along the circumferential direction ( E ). First, we developed a patient-specific semi-automatic approach to estimate its expected value and standard deviation. To this end, pressure-length curves were derived from magnetic resonance images acquired during the cardiac cycle and information on vessel pressure obtained by catheterization. Then, the estimates of E were derived through a maximum likelihood estimation approach based on a vessel constitutive law. In particular, we analyzed the entire PA boundary and an arc free from surrounding organs. Second, we applied the approach to the study of pulmonary endarterectomy (PEA) for the treatment of chronic thromboembolic pulmonary hypertension (CTEPH). We observed a decrease in the circumferential E after PEA for the whole boundary, while no clear trend was observed for the free arc. The low standard deviations associated with the estimates showed high accuracy when considering the entire boundary, while greater variability was observed for the free arc, which was however limited. Finally, reliable hysteretic behavior was obtained from the reconstructed pressure-length curves.